Effects of social media use on psychological well-being: a mediated model - Ostic, Dragana; Qalati, Sikandar Ali; Barbosa, Belem; Muhammad Shah, Syed Mir; Galván Vela, Esthela; Ahmed Muhammad, Herzallah; Feng, Lui (My University, 2021)
The growth in social media use has given rise to concerns about the impacts it may have on users' psychological well-being. This paper's main objective is to shed light on the effect of social media use on psychological well-being. Building on contributions from various fields in the literature, it provides a more comprehensive study of the phenomenon by considering a set of mediators, including social capital types (i.e., bonding social capital and bridging social capital), social isolation, and smartphone addiction. The paper includes a quantitative study of 940 social media users from Mexico, using structural equation modeling (SEM) to test the proposed hypotheses. The findings point to an overall positive indirect impact of social media usage on psychological well-being, mainly due to the positive effect of bonding and bridging social capital. The empirical model's explanatory power is 45.1%. This paper provides empirical evidence and robust statistical analysis that demonstrates both positive and negative effects coexist, helping to reconcile the inconsistencies found so far in the literature. RESUMEN El crecimiento en el uso de las redes sociales ha generado preocupaciones sobre los impactos que puede tener en el bienestar psicológico de los usuarios. El principal objetivo de este artículo es arrojar luz sobre el efecto del uso de las redes sociales en el bienestar psicológico. Sobre la base de las contribuciones de varios campos en la literatura, proporciona un estudio más completo del fenómeno al considerar un conjunto de mediadores, incluidos los tipos de capital social (es decir, el capital social de unión y el capital social puente), el aislamiento social y la adicción a los teléfonos inteligentes. El documento incluye un estudio cuantitativo de 940 usuarios de redes sociales de México, utilizando modelos de ecuaciones estructurales (SEM) para probar las hipótesis propuestas. Los hallazgos apuntan a un impacto indirecto positivo general del uso de las redes sociales en el bienestar psicológico, principalmente debido al efecto positivo de vincular y unir el capital social. El poder explicativo del modelo empírico es del 45,1%. Este documento proporciona evidencia empírica y un análisis estadístico sólido que demuestra que los efectos positivos y negativos coexisten, lo que ayuda a reconciliar las inconsistencias encontradas hasta ahora en la literatura.
Frontiers in Psychology
Keywords: Smartphone addiction; Social isolation; Bonding social capital; Bridging social capital; Phubbing; Social media use; Sistemas